FACTORS INVOLVED IN THE STOMATOGNATHIC PATHOLOGY SYSTEM IN THE ELDERLY AND IMPLICATIONS IN THE PROSTHETIC REHABILITATION-OVERVIEW - Irina Grădinaru; Macovei Georgiana; Loredana Liliana Hurjui; Balcoș Carina; Mihaela Mitrea; Armencia Oana Adina; Magda Ecaterina Antohe (Romanian Dental Association for Education, 2021)
Most authors who have been concerned with the pathology of the stomatognathic system and the factors that influence it (involution of stomatognathic structures, associated systemic diseases) claim that, despite recent therapeutic advances in dentistry that solve multiple morphofunctional problems, they also cause many secondary phenomena. The involvement of systemic factors in the pathology of the elements of the stomatognathic system requires the knowledge of the main characteristics of the general pathology of the elderly that influences the condition of the component segments of the system. Epidemiological studies regarding the incidence and the prevalence of affection offenses generated by the removable prostheses show the importance of the local factors generating negative effects in full agreement with the intensity, duration and correlating their action . The oral cavity reflects as a mirror the existence of clinical manifestations caused by systemic risk factors, and can often become their "primary alarm signal" or "primary diagnostic key" .The dentist must be prepared to observe obvious general clinical changes that may occur during the therapeutic act, changes that may indicate an aggravation of the general status and may induce some therapeutic risks. At their origin are the excessive stresses exerted on the residual ridge by the natural teeth present in the mandible, within the combined syndrome that we mentioned, but also the inappropriate occlusal relations.Histological and histochemical studies have shown the presence of severe fibrosis, inflammation and resorption of the underlying bone .